(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The miracle is an Evidence and proof of the prophethood of the Prophet (peace be upon him), who comes with it, and no human being can come up with the like of it. Because it is from Allah Almighty, and the miracle is dedicated to the prophets and messengers of Allah Almighty, to be evidence of the correctness of their prophethood and message for which they were sent to the nations, and it is a statement of the Unification of Allah Almighty, and that the miracle of the Prophet Muhammad - may Allah’s prayers and peace be upon him - is the Noble Qur’an, and humans could not They come out with one surah or a verse like it, and there is another definition of miracles, which many scholars have found, which is that a miracle is the occurrence of a certain thing by which Allah Almighty supports the person who will carry the call and prophecy, to challenge with it everyone who stands in the face of his call, for it is a trust that the Prophet and the Messenger bear.